2022
DOI: 10.1021/acs.jpclett.2c02138
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Modulation Depth of GdIII-Based Pulsed Dipolar EPR Spectroscopy (PDS) with Porphyrin–GdIII Laser-Induced Magnetic Dipole Spectroscopy

Abstract: Distance determination with pulsed EPR has become an important technique for the structural investigation of biomacromolecules, with double electron–electron resonance spectroscopy (DEER) as the most important method. GdIII-based spin labels are one of the most frequently used spin labels for DEER owing to their stability against reduction, high magnetic moment, and absence of orientation selection. A disadvantage of GdIII–GdIII DEER is the low modulation depth due to the broad EPR spectrum of GdIII. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Photo-excited triplet labels attract increasing attention due to their unique spectroscopic properties. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] The key feature of the photo-excited triplet states is a nonequilibrium electron spin polarization formed upon singlet-triplet intersystem crossing (ISC). 17,18 If this electron spin polarization is strong (called hyperpolarization), the intensity of the EPR signal of the triplet state may significantly exceed that of stable radicals, thus allowing highly sensitive experiments on photo-labels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Photo-excited triplet labels attract increasing attention due to their unique spectroscopic properties. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] The key feature of the photo-excited triplet states is a nonequilibrium electron spin polarization formed upon singlet-triplet intersystem crossing (ISC). 17,18 If this electron spin polarization is strong (called hyperpolarization), the intensity of the EPR signal of the triplet state may significantly exceed that of stable radicals, thus allowing highly sensitive experiments on photo-labels.…”
Section: Introductionmentioning
confidence: 99%
“…3,7 Almost any chromophore in the triplet state can be used as an optically pumped partner in this modification of DEER called LaserIMD, even if it has a broad EPR spectrum and low electron spin polarization. 1,3,5,8,9,14,15 Thus, photo-labels can be used either as observer spins or pumped spins in PDS experiments, both providing decent advantages relative to common (stable) paramagnetic labels.…”
Section: Introductionmentioning
confidence: 99%
“…The photolabels offer the ability to detect a highly intense polarized signal [50][51][52][53][54] or employ a laser pulse instead of a microwave pumping pulse. 49,52,[55][56][57][58][59][60] Except for spectroscopic advantages, LiPDS makes it possible to look at the structure of biological complexes that contain photosensitizers in novel ways. For instance, it has been demonstrated that LiPDS together with other EPR techniques provides insights into the structure and function of photosensitizer complexes with human serum albumin, which hold promise for photodynamic therapy applications.…”
Section: Introductionmentioning
confidence: 99%
“…Light-induced PDS methods have been developed based on the photogenerated triplet state of a 5­(4′-carboxyphenyl)- 10,15,20- triphenylporphyrin (TPP) moiety as photoswitchable spin-label, allowing measurement of its dipolar interaction with permanent paramagnetic centers, e.g., nitroxide, in synthetic model peptides ,, and heme-containing proteins. , The triplet can be used for detection and the permanent paramagnetic center pumped, as in light induced DEER, or the triplet state generated during the pulse sequence and the permanent paramagnetic center detected, as in laser-induced magnetic dipole spectroscopy . Subsequent studies replaced TPP with other chromophores. The photogenerated triplet is advantageous over permanent paramagnetic centers due to its strong spin polarization .…”
mentioning
confidence: 99%